The morphological and ecological variation of Arctostaphylos (Ericaceae) fruit: A link between plant ecology and animal foraging behavior. Issue 3 (15th March 2023) - Crowe, Rebecca E.; Parker, V. Thomas
Abstract: Persistent soil seed banks are characteristic of Arctostaphylos (Ericaceae) species in the Mediterranean‐climate California Floristic Province. While most species are obligate seeders, regeneration of stands of all Arctostaphylos species ultimately depends on post‐fire seedling recruitment. Arctostaphylos seed banks are created, in large part, by scatter‐hoarding rodents. Variation in fruit morphology, therefore, is expected to impact the Arctostaphylos –rodent interaction. Seeds produce sufficient rewards (nutritious mature embryo) to entice rodents to disperse and ultimately bury seeds in the soil. Hard seed coats increase the time required to extract the embryo, encouraging rodents to choose storage over immediate predation, and nutlets are frequently empty. We assessed the variation of fruit nutlet fusion and seed viability among 38 Arctostaphylos taxa. Factors such as latitude, elevation, life history, ploidy, and phylogenetic position were also analyzed. Generalized mixed‐effects models were used to determine the factors contributing to variation in fruit nutlet fusion and seed viability. Our results indicate that fruit volume and shape are the most important variables affecting nutlet fusion and seed viability. Additionally, other potential influences only show a weak correlation and are not predicted to significantly impact nutlet fusion or seed viability. These findings provide insights into evolved strategies used by plants to increase reproductive success via scatter‐hoarding rodents. Our study benefits the conservation and restoration of Arctostaphylos stands by emphasizing the importance of animal‐mediated dispersal and providing estimates of seed viability for different species. With the anticipated effects of climate change, such as departures from historic fire regimes, the preservation of the relationship between plants and animal foragers is crucial for the continued survival of Arctostaphylos and California's evergreen chaparral. Abstract : We assessed the variation of fruit nutlet fusion and seed viability among 38 Arctostaphylos taxa. Our results indicate that fruit volume and shape are the most important variables affecting nutlet fusion and seed viability. These findings provide insight into evolved strategies used by plants to increase reproductive success via scatter‐hoarding rodents.